Is the knowledge of contact force beneficial in pulmonary vein antrum isolation?. (4th May 2017) - Borregaard, Rune; Jensen, Henrik Kjærulf; Tofig, Bawer Jalal; Thrysøe, Samuel Alberg; Gerdes, Christian; Nielsen, Jens Cosedis; Lukac, Peter
Abstract: Objective: To investigate the effect of the operator knowing the real-time contact force (CF) on the efficacy of pulmonary vein antrum isolation (PVAI). Methods: Fifty patients with paroxysmal atrial fibrillation (AF) or short lasting persistent AF were randomized to CF guided PVAI ( n = 25) or conventional PVAI ( n = 25). In the CF guided group, CF between 10 and 40 g was aimed at. Efficacy of PVAI was measured as reduction in AF burden (AFB) and time to AF recurrence detected by implantable cardiac monitor (ICM), inserted three months before PVAI. Blanking period was three months and follow-up 12 months. Results: All pulmonary veins were isolated in the CF guided group and all but one in the conventional group. Mean CF was 25 g in the CF guided group and 24 g in the conventional group ( p = 0.75). Compared to pre-ablation, median [IQR] relative reduction in AFB 3–12 months after ablation was 100 [99–100]% in the CF guided group ( p < 0.001) and 99.4 [25–100]% in the conventional group ( p < 0.001), not different between groups ( p = 0.09). Nine patients (36%) had AF recurrence in the CF guided group and 13 (52%) in the conventional group ( p = 0.21, log-rank test). CF differed between operators. When adjusted for operator by regression analysis, patients without recurrent AF had lower proportion of ablation time with CF <10 g than recurrent patients ( p = 0.034). No complications occurred. Conclusions: Operator knowledge of real-time CF had no significant effect on AFB reduction or time to AF recurrence. Larger trials should be done to study benefit of real-time CF.